The Implications of Closing Civic Space for Hunger and Poverty in the Global South. (31st July 2021) - Hossain, Naomi; Oosterom, Marjoke
Abstract: Concerns about closing civic space have focused on human rights, and little to date has been known of the impacts on development. This article traces impacts of closing civic space on civil society and social movements addressing poverty and hunger in Brazil, Ethiopia, Pakistan and Zimbabwe. Countries that clamped down on civil society and social movements have not all fared badly in terms of poverty and hunger, as the 'developmental states' of China and Vietnam demonstrate. This article proposes that how closures of civic space affect development outcomes will depend on the role civil society plays in development, and specifically on the 'fit' between civil society and the state with respect to development policy and programming. Despite diversity in political and economic context, restrictions on civic space commonly prevent broad civic engagement in policy processes, in particular critique or scrutiny of government policy and practice, and hamper non‐governmental organizations' service delivery. Because civic engagement matters most for marginalized and disempowered people, their exclusion from policy processes and services will deepen. Reversals or stagnation in progress towards addressing poverty and hunger indicate that as civic space narrows, the most marginalized and disempowered groups face a growing risk of being left behind.